SMAC Mimetics as Therapeutic Agents in HIV Infection - Molyer, Bengisu; Kumar, Ashok; Angel, Jonathan B. (Frontiers in Immunology, 2021)
Although combination antiretroviral therapy is extremely effective in lowering HIV RNA to undetectable levels in the blood, HIV persists in latently infected CD4+ T-cells and persistently infected macrophages. In latently/persistently infected cells, HIV proteins have shown to affect the expression of proteins involved in the apoptosis pathway, notably the inhibitors of apoptosis proteins (IAPs), and thereby influence cell survival. IAPs, which are inhibited by endogenous second mitochondrial-derived activators of caspases (SMAC), can serve as targets for SMAC mimetics, synthetic compounds capable of inducing apoptosis. There is increasing evidence that SMAC mimetics can be used to reverse HIV latency and/or kill cells that are latently/persistently infected with HIV. Here, we review the current state of knowledge of SMAC mimetics as an approach to eliminate HIV infected cells and discuss the potential future use of SMAC mimetics as part of an HIV cure strategy.